Health Education Regarding Community Flood Disaster Mitigation in Lepo-Lepo Village - Hasrima; Romantika, I Wayan; Narmawan; Ananda, Siti Hadrayanti; Narmi; Abadi, Eliyani (Community Development Journal, 2024)
Introduction: Natural disasters that often occur in the community are events that always make people feel threatened and disrupt life. One of the natural disasters that always threatens the community is flooding. Communities located in the downstream area of the river will feel threatened at any time. Therefore, it is necessary to provide knowledge about flood disaster mitigation. The purpose of community service is to increase community knowledge about disaster mitigation in the community in lepo-lepo village. Method: Community service activities are carried out through providing education. Results: after being given health education, participants were able to understand the material presented and the level of knowledge of the participants was in the good category. hope that this health education can provide benefits to all communities in Lepo-lepo village, especially vulnerable groups of the elderly. Conclusion: Community service activities by providing health education can increase the knowledge of the elderly about flood disaster mitigation.